Curcumin Induces Ferroptosis in Follicular Thyroid Cancer by Upregulating HO-1 Expression. (14th January 2023) - Chen, Huanjie; Li, Zhoufan; Xu, Jingchao; Zhang, Ning; Chen, Junzhu; Wang, Guangzhi; Zhao, Yongfu
Abstract : Follicular thyroid cancer (FTC) is a highly aggressive type of endocrine malignancy. It is necessary to investigate the mechanisms of tumorigenesis and therapeutic pathways in patients with FTC. Haem oxygenase-1 (HO-1) can regulate oxidative stress and the occurrence of tumors and diseases. In this study, we discovered that HO-1 was abnormally overexpressed in FTC compared with adjacent tissues. However, the HO-1 overexpression was demonstrated to decrease cell viability and to potentially activate the ferroptosis signalling pathway. Ferroptosis is a newly identified form of oxidative cell death and is currently being targeted as a new cancer treatment. Tumorigenesis is significantly inhibited by curcumin. The present study shows that curcumin inhibits the growth of FTC by increasing the HO-1 expression, further activating the ferroptosis pathway. This study demonstrates that the HO-1-ferroptosis signalling pathway might play an important role in FTC tumorigenesis, and that curcumin inhibits the growth of FTC cells by affecting this pathway.